ETHNOMATHEMATICS EXPLORATION PETILASAN SRI AJI JAYABAYA KEDIRI DISTRICT - Kristianti, Lina; Jatmiko, Jatmiko (PROGRES PENDIDIKAN, 2024)
Study This done for explore elements​​ mathematics (ethnomathematics) in Petilasan Sri Aji Jayabaya. Method used in study This that is descriptive qualitative with approach ethnography. Data used is the data obtained through studies literature; observation; interview; and documentation. Data analysis techniques using Miles and Huberman's methods include data reduction, data presentation, as well Conclusion drawing and verification. Aspect culture from Reminiscences of Sri Aji Jayabaya obtained from studies literature and interviews. Aspect mathematical from Reminiscences of Sri Aji Jayabaya obtained from results observations made.​ Documentation Alone used as supporting data that has been obtained through studies literature; interview; and observation. Result of study This is there is elements​​ mathematics (ethnomathematics) in Petilasan Sri Aji Jayabaya; that is draft mirroring; get up room side flat; get up room side curved; and wake up flat.